Work Coordination as a Social Interaction Process in Nursing Staff Meetings - Pennanen, Eveliina; Mikkola, Leena (Nordic Journal of Working Life Studies, 2016)
Work coordination, which here refers to organizing, planning, discussing, and negotiating work, is done through social interaction. Because coordination is essential to work quality and well-being at work, it is important to understand the processes that construct work coordination. This study aims to understand work coordination as a social interaction process by analyzing social interaction in nursing staff meetings of a Finnish hospital. Observations and approaches of inductive and descriptive qualitative analysis were used to examine eight sequential nursing staff meetings that took place in 2012. The results indicate that work coordination consisted of sense-making information, sense-making action, managing emotions, and managing positions of employees. Work coordination constructs the social reality of the workplace both on the task level and the relational level. Understanding that work coordination is not only a task-oriented process that deals with organizing practical tasks and duties but is also a process of constructing positions and relationships in work communities helps to identify and understand the possibilities that social interaction and its practices, such as workplace meetings, offer. The findings can be applied in the organizational context to evaluate and develop workplace interactions.